2012
DOI: 10.1186/1477-7819-10-105
|View full text |Cite
|
Sign up to set email alerts
|

Limb salvage in osteosarcoma using autoclaved tumor-bearing bone

Abstract: BackgroundTumor prostheses currently give the best short- and medium-term results for limb-salvage reconstruction procedures in the treatment of bone tumors. However, in developing countries, the cost of a tumor prosthesis is beyond the reach of much of the population. We report the use of autoclaved tumor-bearing bone in 10 patients, as an affordable alternative to the use of prostheses.MethodsThis is a case series of 10 patients (mean age 19 years) with osteosarcoma who were treated at our hospital from 1998… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Compared with other recycling autograft procedures, those in the current study had better or comparable union times and union rates ( Table 2). 5,6,[8][9][10]13,14,[19][20][21][22][23][24][25][26][27][28] It has been reported that the disadvantages of osteoarticular grafts are late osteoarthritis change and subchondral bone collapse, problems leading to tumor prosthesis revision or arthrodesis. The allograft-prosthesis composite was developed to prevent this problem, 4 and thesis survival rates, and complication rates for the current authors' procedures vs those of other procedures used for tumor reconstruction (allograft-prosthesis composite, extracorporeal autograftprosthesis composite, pasteurization autograft-prosthesis composite) is shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other recycling autograft procedures, those in the current study had better or comparable union times and union rates ( Table 2). 5,6,[8][9][10]13,14,[19][20][21][22][23][24][25][26][27][28] It has been reported that the disadvantages of osteoarticular grafts are late osteoarthritis change and subchondral bone collapse, problems leading to tumor prosthesis revision or arthrodesis. The allograft-prosthesis composite was developed to prevent this problem, 4 and thesis survival rates, and complication rates for the current authors' procedures vs those of other procedures used for tumor reconstruction (allograft-prosthesis composite, extracorporeal autograftprosthesis composite, pasteurization autograft-prosthesis composite) is shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…4 Allografts are not available in some areas and have a high complication rate. There are many techniques used for recycling autografts, such as extracorporeal radiation, 5,6 pasteurization, 7,8 autoclaving, 9,10 and freezing. 11 The advantages of recycling autografts are good availability, no requirement of bone bank, biological reconstruction, no disease transmission, less immunological response, soft tissue and ligament attachment, and availability of a massive bone stock.…”
mentioning
confidence: 99%
“…The limitations of tumor prosthesis are long‐term survival of the prosthesis and their high cost. Most patients in developing countries cannot afford this type of reconstruction and are treated by amputation even if they are technically eligible for limb salvage …”
Section: Introductionmentioning
confidence: 99%
“…The success of eradicating tumour cells by autoclaving has also been endorsed by Pan [15] in the management of osteosarcomas.…”
Section: Review Of Literaturementioning
confidence: 98%